Compensation of Respiratory-Related Postural Perturbation Is Achieved by Maintenance of Head-to-Pelvis Alignment in Healthy Humans - Attali, Valérie; Clavel, Louis; Rouch, Philippe; Rivals, Isabelle; Rémy-Néris, Ségolène; Skalli, Wafa; Sandoz, Baptiste; Similowski, Thomas (Frontiers in Physiology, 2019)
The maintenance of balance in healthy humans requires the preservation of an horizontal gaze, best achieved through dynamical adjustments of spinal curvatures and pelvic tilt that keep the head-to-pelvis alignment close to the vertical. It is currently unknown whether the spinal and pelvic compensations of respiratory-related postural perturbations are associated with preservation of the head-to-pelvis vertical alignment. We tested this hypothesis through the comparison of postural alignment variables at extreme lung volume (total lung capacity, TLC; residual volume, RV) with their reference value at functional residual capacity (FRC). Forty-eight healthy subjects (22 women; median age of 34 [26; 48] years) were studied using low dose biplanar X-rays (BPXR; EOS® system). Personalized three-dimensional models of the spine and pelvis were reconstructed at the three lung volumes. Extreme lung volumes were associated with changes of thoracic curvature bringing it outside the normal range. Maximal inspiration reduced thoracic kyphosis (T1-T12 angle=47° [37; 56], -4° variation [-9; 1], p=0.0007) while maximal expiration induced hyperkyphosis (T1-T12 angle=63° [55; 68]; +10° variation [5; 12], p=9x10-12). Statistically significant (all p<0.01) cervical and pelvic compensatory changes occurred (C3-C7 angle: +4° [-2; 11] and pelvic tilt +1° [0; 3] during maximal inspiration; C3-C7 angle: -7° [-18;-1] and pelvic tilt +5° [1; 8] during maximal expiration), resulting in preserved head-to-pelvis alignment (no change in the angle between the vertical plane and the line connecting the odontoid process and the midpoint of the line connecting the centre of the two femoral heads ODHA). Lung volume related postural perturbations were more marked as a function of age, but age did not affect head-to-pelvis alignment. These findings should help understand balance alterations in patients with chronic respiratory diseases modifying lung volume and rib cage geometry.